2019
DOI: 10.1109/lra.2019.2928206
|View full text |Cite
|
Sign up to set email alerts
|

Contact-Based Bridge Inspection Multirotors: Design, Modeling, and Control Considering the Ceiling Effect

Abstract: This paper presents the design, modelling and control of a multirotor for inspection of bridges with full contact. The paper analyzes the aerodynamic ceiling effect when the aerial robot approaches the bridge surface from below, including its aerodynamic characterization using Computational Fluid Dynamics (CFD). The proposed multirotor design takes the modelled aerodynamic effects into account, improving the performance of the aerial platform in terms of the stability and position accuracy during the inspectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…We chose this scenario because it is particularly hard for an observer to accurately estimate the distance from a featureless object in front of them. Nonetheless, ordinary tasks such as inspection and navigation in confined environments require to approach walls to examine them while preventing collisions [29]. Task 2 and 3 consist, respectively, of going through a lateral or vertical opening, placed perpendicularly to the user's sight.…”
Section: Qlmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose this scenario because it is particularly hard for an observer to accurately estimate the distance from a featureless object in front of them. Nonetheless, ordinary tasks such as inspection and navigation in confined environments require to approach walls to examine them while preventing collisions [29]. Task 2 and 3 consist, respectively, of going through a lateral or vertical opening, placed perpendicularly to the user's sight.…”
Section: Qlmentioning
confidence: 99%
“…Despite the recent scientific and industrial interest for motion-based interfaces and haptic feedback for the control of aerial robots, a study of the real usability of such systems in real-world cases is still lacking. To fill this gap, we present a systematic approach to provide more insights on how effective is controlling a drone through hand motion and the role of haptics in augmenting the performance in particular tasks, which are fundamental in several scenarios such as search-and-rescue or inspection [29]- [31]. In this paper, we first investigate the effects of a paradigm shift for robot teleoperation consisting of mapping the position of the user's hand into a position command for the robot, as in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, there are three main approaches for infrastructure contact inspection. One of them consists of using a multirotor which can stick firmly to the bridge beams and place a reflector prism in contact with the bridge surface to measure beam deformation using a robotic Total Station on ground, which can measure the position of the prism with millimeter accuracy [ 21 ]. The main advantage of this approach is that the measurements can achieve the required accuracy for structural assessment since the robot is completely still while the inspection measurements are collected.…”
Section: Introductionmentioning
confidence: 99%
“…Aerodynamic effects can arise also in these kinds of scenarios and applications, in which the aerial robot is required to operate in the surrounding of the infrastructure. Previous works have shown how the aerodynamic ceiling effect can change the performance of a multirotor when it approaches a surface from the underside [ 41 , 42 ] and usually requires using a specific controller [ 21 , 43 ]. However, in this specific work, the system will operate far enough from the infrastructure not to be affected by this aerodynamic disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…These aerodynamic effects have been previously studied [11] [12][13] [14] and also by the authors. In [15] a general overview of these kinds of effects was presented and some of them were specifically studied for different applications like the ground effect in [16] or ceiling effect in [6] [17]. These previous studies have shown that it is usually necessary to model this aerodynamic behaviour to guarantee that the final application produces a results which are good enough even flying very close to obstacles.…”
mentioning
confidence: 99%